Efektivitas Sitangkot dalam Pemuktakhiran Data Pemilih Berkelanjutan pada Komisi Pemilihan Umum Kota Tangerang - Atika Maharani Tasya; Mawar Mawar; Abdul Rahman (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2022)
The result which helps the people of Tangerang city to be more concerned with voter data so that no duplicate or unregistered voter lists are found during the general descriptive type of research. Data collection techniques: indicator or relative advantage that the innovation of the information stem of the Tangerang General Election Commission data has advantages and is useful for accelerating and facilitating the community and related institutions in sustainable voter data, then from the compatibility indicator, it helps the community by not Opening the sheet again, directly accessing the SITANGKOT application to check voter data, from the complexity indicator the SITANGKOT application reduces people who come directly to the KPU office if there is a problem because in the application there is a data request feature in the triability indicator and the steps in the application are already in the guide feature in the SITANGKOT application using language that is easy for the public to understand, indicators of observability in accessing the SITANGKOT application, the need for good internet network access so that it can be maximized and also if there is a change in the KPU processing 3x24 hours and there is a system cleaning at 12 o'clock at night.